EFEKTIVITAS MODEL GAMIFICATION IN EDUCATION TERHADAP KREATIVITAS PESERTA DIDIK PADA PEMBELAJARAN IPA DITINJAU DARI LITERASI TEKNOLOGI - Endah Purwaningsih; Sarwanto Sarwanto; Winarno Narmoatmojo (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Students' creativity in science learning is still the main challenge amid the demands of 21st-century learning that emphasizes the ability to think innovatively and adaptively to technology. Low technological literacy and conventional pedagogical approaches that do not actively involve students are the two dominant obstacles in fostering students' creativity. This study aims to analyze the effectiveness of the Gamification in Education model on the creativity of elementary school students from the level of technological literacy. Using a 2x2 factorial pseudo-experiment design, as many as 54 grade VI students from five elementary schools in Wonogiri Regency were divided into experimental and control groups based on learning models and technology literacy categories. The results showed that the gamification model significantly increased students' creativity (F = 824.7991; p = 0.000), especially in the group with high technology literacy who recorded the highest scores. Technology literacy also makes a positive contribution to creativity achievement (F = 129.9946; p = 0.000). In addition, there was a significant interaction between the learning model and technological literacy (F = 31.3306; p = 0.000), indicating that the technological readiness of students strongly influences the effectiveness of gamification.